EFEKTIVITAS PENERAPAN SISTEM E-PLANNING PROGRAM PEMBANGUNAN DAERAH PADA BAPPEDA LITBANG KOTA PALEMBANG - Putra Trimbawan; Kemas Muhammad Iqbal; Masayu Syawalia Agustina; Mardian Suherli; Riza Adrianto (MAP Program Pascasarjana Universitas Sjakhyakirti, 2022)
This study aims to find out how the implementation of e-Planning at the Research and Development Agency of Palembang City in preparing development planning in Palembang City. This study uses qualitative methods in essence to observe directly and use interviews to explore problems related to research. Data collection techniques used in this study were interviews, and direct observation. In-depth interviews were conducted with key informants intended to obtain in-depth information about e-planning policies. This study concludes that, the effectiveness of the implementation of the e-Planning System of the Research and Development Agency of Palembang City most of the achievement of proposing program activities from the OPD has been carriead out well, the obstacles in implementing the e-planning system include some employees who are not capable and understand, and lack of integrated with each other